1996
DOI: 10.1038/383089a0
|View full text |Cite
|
Sign up to set email alerts
|

Control of calcium oscillations by phosphorylation of metabotropic glutamate receptors

Abstract: Stimulation of two metabotropic glutamate-receptor subtypes, mGluR1 and mGluR5, triggers the release of Ca2+ from intracellular stores through the inositol-(1,4,5) trisphosphate (InsP3) pathway. Here we report that glutamate induces single-peaked intracellular Ca2+ mobilization in mGluR1alpha-transfected cells but elicits Ca2+ oscillations in mGluR5a-transfected cells. The response patterns of the intracellular Ca2+ increase depend upon the identity of a single amino acid, aspartate (at position 854) or threon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
251
2
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 267 publications
(269 citation statements)
references
References 28 publications
15
251
2
1
Order By: Relevance
“…HEK 293 cells transfected with mGluR1a revealed, upon stimulation, fast transient [Ca 2+ ] i increases. Similar responses have been reported in HEK 293 cells expressing mGluR1a (Kawabata et al, 1996;Gomeza et al, 1996;Flor et al, 1996) and in CHO cells transfected with mGluR1b (Knopfel et al, 1995). In contrast, the analysis of Ca 2+ responses in HEK 293 cells expressing mGluR5a revealed [Ca 2+ ] i oscillations in almost all cells that were able to respond to agonists.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…HEK 293 cells transfected with mGluR1a revealed, upon stimulation, fast transient [Ca 2+ ] i increases. Similar responses have been reported in HEK 293 cells expressing mGluR1a (Kawabata et al, 1996;Gomeza et al, 1996;Flor et al, 1996) and in CHO cells transfected with mGluR1b (Knopfel et al, 1995). In contrast, the analysis of Ca 2+ responses in HEK 293 cells expressing mGluR5a revealed [Ca 2+ ] i oscillations in almost all cells that were able to respond to agonists.…”
Section: Discussionsupporting
confidence: 82%
“…Untransfected HEK 293 and CHO cells do not express endogenous metabotropic or ionotropic glutamate receptors functionally coupled to PLC and intracellular Ca 2+ mobilization (Gabellini et al, 1994;Kawabata et al, 1996;Daggett et al, 1995). In transfected cells activation of mGluR1a and mGluR5a elicits different patterns of intracellular Ca 2+ responses suggesting that these two receptors play distinct roles in intracellular Ca 2+ homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…The rhythmic activity induced by mGluR activation in type I and type II interneurons, which is most likely mGluR1-mediated, is independent of the previously reported intracellular Ca 2ϩ oscillations, which were shown to be mGluR5-dependent (Kawabata et al, 1996). Hence, one would predict the absence of Ca 2ϩ oscillations in type II interneurons because they express mGluR1 only.…”
Section: Discussionmentioning
confidence: 70%
“…We have recently reported that mGluRl and mGluR5, although both coupling to the IP3/Ca 2~cas-cade, induce distinct [Ca2~] 1responses in the heterologous expression system (Kawabata et al, 1996). In both HEK293 and NIH3T3 cells, mGluRl shows a single-peaked, nonoscillatory [Ca 2~I~response to glutamate application, whereas mGluR5 evokes an oscillatory [Ca2~] 1 response by glutamate exposure.…”
mentioning
confidence: 99%